A comparative study of dynamic adsorption of anionic synthetic and nanocellulose-based surfactant in Malaysian reservoir - Muhammad Ayoub; Mysara Eissa Mohyaldinn; Syed Mohammad Mahmood; Aqsha Aqsha; Shiferaw Regassa Jufar; Sarah Farrukh; Farrukh Inayat; Muhammad Rashid Shamsuddin (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract This project is aimed at studying the applicability of nanocellulose-based surfactant as a sustainable surfactant for enhanced oil recovery process (EOR) in Malaysia. Abundant biomass waste from palm oil industry in Malaysia is hard to be disposed of. Therefore, potential application of biomass in chemical EOR is an attractive alternative to minimize these problems. For this study, nanocellulose is synthesized from oil palm empty fruit bunch (OPEFB) and undergoes chemical modification for it to act like a surfactant. All methods and techniques in synthesizing nanocellulose and preparing nanocellulose-based surfactant are made inhouse. While waiting for the material preparation, adsorption study is carried out by using anionic synthetic surfactant. Characterization result shows the nanocellulose undergoes chemical modification successfully. The IFT results for the nanocellulose-based surfactants are also in a good and acceptable range, but there are some limitations in using nanocellulose-synthesized surfactant. The average particle size of nanocellulose is 283.5 µm which is larger than size of the reservoir pore throat. Dynamic adsorption cannot be performed as the large particle size of nanocellulose might plug the porous domains. Therefore, it is recommended to further improve the method of synthesizing nanocellulose from OPEFB because the nanocellulose-based surfactant is expected to have potential of lower adsorption in porous media once it becomes nanosized and due to its advantages such as being of lower cost and environmental friendly compared to other commercial surfactants.